Tantangan dan Peluang Peningkatan Penerbitan Buku Sastra Bali Modern - I Nyoman Darma Putra; I Gde Nala Antara (Jurnal Kajian Bali (Journal of Bali Studies), 2019)
Over the last ten years (2009-2018), the average number of modern Balinese literary books published reached 10.9 titles per year. This data is derived from the number of books nominated for the annual Rancage Literary Award over the last ten years. This research identifies and discusses opportunities and challenges in the development of the publication of modern Balinese literary books nowadays. The research focuses on identifying the supporting factors and challenges of the publication of modern Balinese literary books. Research methods applied in this study were library studies and limited ethnographic research through interviews, especially with stakeholders of modern Balinese literature including writers, readers and book agencies. Data were analyzed by Escarpit’s theory of sociology of literature that proposes the study of literature in the entire environment of literary creation, distribution and consumption. This study concludes that the provincial government of Bali, publishers, literary communities and authors all play an important role in overcoming challenges and taking advantage of opportunities for increasing the publication of modern Balinese literature.